The political impossibility of modern counterinsurgency strategic problems, puzzles, and paradoxes - Smith, M. L. R. (Michael Lawrence Rowan) 1963-; Jones, David Martin 1950- (Columbia studies in terrorism and irregular warfare, 2015)
The counterinsurgency (COIN) paradigm dominates military and political conduct in contemporary Western strategic thought. It assumes future wars will unfold as "low intensity" conflicts within rather than between states, requiring specialized military training and techniques. COIN is understood as a logical, effective, and democratically palatable method for confronting insurgency--a discrete set of practices that, through the actions of knowledgeable soldiers and under the guidance of an expert elite, creates lasting results.Through an extensive investigation into COIN's theories, methods, and outcomes, this book undermines enduring claims about COIN's success while revealing its hidden meanings and effects. Interrogating the relationship between counterinsurgency and war, the authors question the supposed uniqueness of COIN's attributes and try to resolve the puzzle of its intellectual identity. Is COIN a strategy, a doctrine, a theory, a military practice, or something else? Their analysis ultimately exposes a critical paradox within COIN: while it ignores the vital political dimensions of war, it is nevertheless the product of a misplaced ideological faith in modernization